Exploring culture as a paradox: complementary QUEUE analysis of cultural values and practices. Issue 1 (22nd November 2019) - Lowe, Sid; Kainzbauer, Astrid; Hwang, Ki-Soon
Abstract : Purpose: The purpose of this paper is to present the proposition that culture in international management has been dominated by a "Western dualism to measuring culture" (Caprar et al., 2015, p. 1024), which has resulted in severe problems and persistent limitations. The suggestion is that cultural research can be more productively conceived as a paradox involving a duality between two contrasting yet co-determined spheres or domains. Design/methodology/approach: The paper provides an outline of culture as a paradox and an outline of a research approach to address the dualities of culture. Findings: A cultural duality is described, which involves a paradoxical "yin-yang" relationship between two contrasting yet mutually constituted aspects of the collective mind. One domain, which involves conscious cognitive elements has dominated research characterized by positivism and empirical cross-cultural explorations of phenomenological cultural values. The second, more recondite domain, involves unconscious and embodied cultural phenomena, which are more tacit and hidden in indirect expression through communicative interaction, exchanges of symbolic representations and embodied behaviour in context. Research limitations/implications: A methodological duality of qualitative and quantitative mixing in order to provide a bi-focal understanding of both tacit and explicit aspects of culture is proposed as a research agenda. Originality/value: The suggestion is that these cultural shadows have been relatively neglected thus far in cross-cultural management research. This means that in order to better comprehend culture as paradox, an equalization of approaches sensitive to both sides of the duality is prescient. In pursuit of this idea, a complementary qualitative analysis directed at more nebulous cultural phenomena is proposed in order to provide a balanced analysis of culture as paradox.